DendroSync: An R package to unravel synchrony patterns in tree-ring networks - Alday, Josu G.; Shestakova, Tatiana A.; Resco de Dios, Víctor; Voltas, Jordi (Dendrochronologia (Verona), 2018)
Spatial synchrony refers to the presence of a common signal for a time-varying characteristic that, in dendrosciences, is shared among tree-ring chronologies from a particular area. Analysis and interpretation of synchrony patterns in tree-ring networks is currently limited by: (i) the requirement for flexible modelling of complex correlations and heteroscedastic errors and (ii) the availability of ready-to-use open software to fulfil this task. We present an R package (DendroSync) that facilitates estimating and plotting synchrony patterns for pre-defined groups. The package has been devised to work with traits derived from tree rings (e.g. ring-width), but other data types are also suitable. It combines variance-covariance mixed modelling with functions that quantify the degree to which tree-ring chronologies contain a common signal over a fixed time period. It also estimates temporal changes in synchrony using a moving window algorithm. The functionality and usage of DendroSync are illustrated using a simple example.